Photo and electroluminescence of porous silicon layers - Haji-Ali, E (BIBECHANA, 2012)
Porous silicon layers were prepared by both chemical and electrochemical methods on n- and ptype Si substrates. In the former technique, light emission was obtained from p-type and n-type samples. It was found that intense light illumination during the preparation process was essential for PSi formation on n-type substrates.An efficient electrochemical cell with some useful features was designed for electrochemical etching of silicon. Various preparation parameters were studied and photoluminescence emissions ranging from dark red to light blue were obtained from PSi samples prepared on p-type substrates. N-type samples produced emissions ranging from dark red to orange-yellow. Electroluminescence of porous silicon samples showed that the color of the emission was the same as the photoluminescence color of the sample, and its intensity and duration depended on the current density passed through the sample. The effects of exposure of samples to air, storage in vacuum, and heat-treatment in air on luminescence intensity of the samples and preparation of patterned porous layers were also studied. Keywords: Porous silicon layers; photoluminescence; electroluminescence DOI: http://dx.doi.org/10.3126/bibechana.v8i0.4897 BIBECHANA 8 (2012) 46-52